Методика оптимізації лопатевої системи робочого колеса радіально-осьової гідротурбіни - Миронов, Костянтин Анатолійович; Олексенко, Юлія Юріївна (НТУ "ХПІ", 2017)
При модернізації та проектуванні нових робочих коліс радіально-осьових гідротурбін необхідно використовувати комплексний підхід для знаходження найбільш вдалих технологічних рішень. Необхідною початковою точкою є створення геометрії лопаті з високими енергокавітаційними показниками. Для отримання оптимальних результатів розрахунку спроектована лопатева система повинна бути інтегрована, переважно автоматично, в модель САПР. Оптимальні геометричні параметри лопаті визначаються завдяки методиці оптимізації з використанням аналізу взаємодії структури рідини.

The maintenance of hydropower generators is a very important issue. They are designed to operate for several decades and during their lifetime several failures might happen. The maintenance of hydropower generators requires a complete set of process activities to support maintenance decisions. The acquisition of the actual geometry with high energy cavitations performance of the runner blade is a required starting point. Some maintenance geometric features do not have correspondence with design geometric features. In this case, preferably in automatic procedure, the maintenance geometric features must be inserted into the CAD model. Optimal values for maintenance geometric features parameters can be determined by simulation optimization technique using fluid structure interaction (FSI) analysis. Finally, immersive virtual reality facilitates the visualization of the results obtained from the finite element analysis.
Methods optimization blades runner of Francis turbine
Keywords: кавітація; тріщини; лопать; маточина; обід; змішана поверхня; CFD; hydroturbine; runners; blade; hub; shroud; blending surfaces